A proteomic analysis of the ventral and dorsal hippocampal brain areas of serotonin knockout rats - Fairbairn, Lorren R. (Stellenbosch : Stellenbosch University, 2008)
Thesis (MScMedSc (Biomedical Sciences. Medical Physiology)--Stellenbosch University, 2008.